Bioenergy from loeophyllum-Rhizopus fungal biofuel cell - Awang Bakar, Aimi Syahirah; Othman, Raihan; Yahya, Muhd Zu Azhan; Othman, Rashidi; Nik Din, Nik Mohd Suhaimi (Trans Tech Publications, Switzerland, 2012)
Fungal biofuel cell comprising of liquid culture suspension of Gloeophyllum and Rhizopus fungal strains is studied. Gloeophyllum liquid culture forms the anolyte of the microbial fuel cell (MFC) while Rhizopus liquid culture which forms the catholyte. Bioenergy is harvested from biocatalytic redox reactions of glucose/oxygen as a result of metabolic activities of respective fungi. Pyranose-2-oxidase of Gloeophyllum catalyzes oxidation of glucose, whereas laccase produced by Rhizopus catalyzes oxygen reduction. Upon incubation period of 8 days, the Gloeophyllum-Rhizopus MFC is capable to deliver 5 mW of power output continuously for 21 days under uncontrolled, open ambient surroundings. MFC with such performance characteristics is sufficed to power remote sensing devices.